2021
DOI: 10.1038/s41598-021-00456-7
|View full text |Cite
|
Sign up to set email alerts
|

Classification of temporomandibular joint internal derangement based on magnetic resonance imaging and clinical findings of 435 patients contributing to a nonsurgical treatment protocol

Abstract: This prospective clinical study aimed to establish a new classification system for TMJ internal derangement based on MRI in correlation with clinical findings contributing to a nonsurgical treatment protocol. A consecutive sample of 435 internal derangement patients was enrolled in the study. Clinical and MRI studies were used to establish the new classification system. A total of 747 joints were classified according to our staging system and received treatment according to the associated nonsurgical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In case of disc displacement with reduction (DDR) in the closed mouth position, the posterior region of the disk is anterior to the condyle, whereas in the open mouth position, it returns to the normal position. However, in case of disc displacement without reduction (DDWR) in the closed mouth position, the posterior region of the disk is anterior to the condyle, and the disc size is normal, whereas in the open mouth position, the posterior region of the disk cannot return to its normal position between the condyle and articular eminence [ 24 ]. In the disease group/non-treated, MRI images at 0 and 6 months revealed that disc displacement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In case of disc displacement with reduction (DDR) in the closed mouth position, the posterior region of the disk is anterior to the condyle, whereas in the open mouth position, it returns to the normal position. However, in case of disc displacement without reduction (DDWR) in the closed mouth position, the posterior region of the disk is anterior to the condyle, and the disc size is normal, whereas in the open mouth position, the posterior region of the disk cannot return to its normal position between the condyle and articular eminence [ 24 ]. In the disease group/non-treated, MRI images at 0 and 6 months revealed that disc displacement (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are some efforts recently dedicated to the new scoring system, based on the MRI findings as the gold standard. This novel staging system is able to demonstrate the state of the LPM, joint effusion, degenerative disc changes, and disk perforation, as well as bone degeneration and translation of the condyle, and also the integrity of the retrodiscal layers in addition to the direction of disc displacement [ 47 ]. The authors of this system confirmed that patients can be assigned into the right stage of TMD based on these parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Щоб оцінити стан СНЩС та вибрати оптимальний план лікування в залежності від виявлених змін на зображеннях МРТ було обрано найбільш поширену класифікацію за C. H. Wilkes. Він описав розлади, починаючи від безсимптомних нормальних суглобів, пов'язаних із невеликим зміщенням вперед, до прогресуючих випадків, пов'язаних із дегенеративними змінами кісток із серйозними клінічними симптомами [6,7].…”
Section: вступunclassified